Fundamentals of Entrepreneurship (ENT300) : Eskac Paradise/ Azzatul Natasha Ahmad … [et al.] - Ahmad, Azzatul Natasha; Harmy, Nur Sabrina Natasha; Afandi, Dýg Afiqah Shafira (2019)
In this business opportunity, we are given the opportunity to open a business. In order to conduct a business, we need to identify, evaluate and select the business, so that, we can focusing on how we are going to plan and implementing our business, Hence, we are going to make the best Ais Kacang in town. Our shop is called Eskac Paradise which is located at Kota Samarahan area. We will serve the best quality and delicious Ais Kacang that everyone will enjoy with their family, relatives or friends.